ANALYSIS OF MARINE LAW IN THE AREA EXCLUSIVE ECONOMIC ZONE - Agusta, Ardigautama (Jurnal Pendidikan Geografi Gea, 2017)
The Unitary State of the Republic of Indonesia (NKRI) is an archipelago country characterized by the archipelago with its territories and boundaries and rights established by law. As a country that has signed UNCLOS (United Nations Convention on the Law of the Sea), the territorial sea of NKRI is divided into 7 areas, namely Internal Waters, Archipelagic Waters, Territorial Sea, Contiguous Zone, Exclusive Economic Zone (ZEE), Continental Shelf and High Seas. The laws and regulations governing the principles of ZEE are Law 5/1983 on Exclusive Economic Zone, Law 6/1996 on Indonesian Waters and Law 32/2014 on Marine. The method used to perform the analysis is a comparative method, which is to compare between the parameters specified. In ZEE NKRI, other countries also have rights and obligations in laying2 submarine cables and pipelines. This has not been discussed in the Marine Law and should be discussed in the Marine Law in order to preserve the territorial sea of ZEE NKRI.